The Relationship between the Severity of Coronary Artery Disease and Epicardial Adipose Tissue Depends on The Left Ventricular Function - Doesch, Christina (Public Library of Science, 2012)
BACKGROUND: Epicardial adipose tissue (EAT) is an active metabolic and endocrine organ. Previous studies focusing mainly on patients with preserved left ventricular function (LVF) could show a correlation between increased amounts of EAT and the extent and activity of coronary artery disease (CAD). However, to date, there are no data available about the relationship between EAT and the severity of CAD with respect to the whole spectrum of LVF impairment. Therefore, we evaluated this relationship in patients with CAD. METHODS: 250 patients with CAD and 50 healthy controls underwent CMR examination to assess EAT. The severity of CAD was defined using the angiographic Gensini score (GSS). RESULTS: The GSS ranged from 2–364. Linear regression analysis revealed a significant correlation between EAT and GSS (r = 0.177, p = 0.01). Patients with mild (GSS≤10) and moderate CAD (GSS>10−≤40) showed comparable EAT to healthy controls. However, in patients with severe CAD (GSS>40) EAT was significantly reduced (p<0.0001) compared to healthy controls. Interestingly, patients with the same GSS revealed different EAT depending on the left ventricular function (LVF). Patients with preserved LVF (LVF≥50%) showed more EAT mass compared to those with reduced LVF (LVF<50%) regardless of the GSS. In patients with preserved LVF and mild CAD, EAT was comparable to healthy controls (61.8±19.4 g vs. 62.9±14.4 g, p = 0.8). In patients with moderate CAD, EAT rose significantly to 83.1±24.9 g (p = 0.01) and started to decline to 66.4±23.6 g in patients with severe CAD (p = 0.03). Contrary, in CAD patients with reduced LVF, EAT was already significantly reduced in patients with mild CAD as compared to healthy controls (p = 0.001) and showed a stepwise decline with increasing CAD severity. CONCLUSION: The relationship between EAT and the severity of CAD depends on LVF. These findings emphasize the multifactorial interaction between EAT and the severity of CAD.